Gestão de resíduos eletrônicos no Brasil: desafios e oportunidades na perspectiva da economia circular - Souza, Dallissa Katharine Ribeiro Rodrigues de (Universidade Federal de São Carlos, 2025)
The management of electronic waste has become one of the greatest environmental challenges of contemporary times, especially in developing countries such as Brazil. With the significant increase in the consumption of electrical and electronic equipment and the rapid pace of technological obsolescence, the volume of improperly discarded e-waste has grown, generating considerable socio-environmental impacts. In this context, the circular economy emerges as a strategic alternative to the traditional linear model, promoting resource reuse, waste reduction, and the valorization of critical materials. This study aimed to analyze, through a literature review, the main challenges and opportunities related to electronic waste management in Brazil from the perspective of the circular economy. The results revealed that, although the National Solid Waste Policy (PNRS) represented an important legal milestone, its effective implementation still faces barriers such as lack of inspection, low public awareness, and limited infrastructure for selective collection and recycling. On the other hand, initiatives in remanufacturing, urban mining, the use of digital technologies, and the role of cooperatives have shown potential to optimize the reverse chain and boost circularity. The research also highlighted the importance of articulation among government, the productive sector, and civil society to strengthen sustainable practices. It is concluded that the transition to a circular economy in the management of electronic waste in Brazil requires regulatory advances, investments in technological innovation, environmental education programs, and incentives for shared responsibility. Only through an integrated approach will it be possible to minimize environmental impacts, promote social inclusion, and foster a more sustainable development model.
Electronic waste management in Brazil: challenges and opportunities from a circular economy perspective
Keywords: Resíduos eletrônicos; Economia circular; Logística reversa; Sustentabilidade; Electronic waste; Circular economy; Reverse logistics; Sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA